2014
DOI: 10.1093/brain/awu279
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy predicts nuclear gene defect in patients with mitochondrial ophthalmoplegia

Abstract: Mitochondrial ophthalmoplegia is a genetically heterogeneous disorder. Horga et al. investigate whether peripheral neuropathy can predict the underlying genetic defect in patients with progressive external ophthalmoplegia. Results indicate that neuropathy is highly predictive of a nuclear DNA defect and that it is rarely associated with single mitochondrial DNA deletions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…Overall, peripheral neuropathy was rare in our cohort (&4 %), coherently with the notion that neuropathy is rare in patients with mtDNA single deletion, especially compared with mitochondrial diseases due to other etiologies [24].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, peripheral neuropathy was rare in our cohort (&4 %), coherently with the notion that neuropathy is rare in patients with mtDNA single deletion, especially compared with mitochondrial diseases due to other etiologies [24].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 67% of PEO patients had a single mitochondrial DNA deletion, whereas 10% had a point mutation of mtDNA and 22% had mutations in either POLG, C10orf2, RRM2B, or had multiple mtDNA deletions in muscle without an identified nuclear gene defect. The prevalence of peripheral neuropathy was significantly lower in patients with single, sporadic mitochondrial DNA deletion (2%) as compared to those with a mtDNA point mutation or with a nuclear DNA defect (44% and 52%, respectively; P < 0.001) [10]. Therefore, our results confirm the suggestion by Horga et al, that in PEO patients peripheral neuropathy is rarely found in association with single mtDNA deletions, whereas it is highly predictive of an underlying nuclear DNA defect [10,11].…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of peripheral neuropathy was significantly lower in patients with single, sporadic mitochondrial DNA deletion (2%) as compared to those with a mtDNA point mutation or with a nuclear DNA defect (44% and 52%, respectively; P < 0.001) [10]. Therefore, our results confirm the suggestion by Horga et al, that in PEO patients peripheral neuropathy is rarely found in association with single mtDNA deletions, whereas it is highly predictive of an underlying nuclear DNA defect [10,11]. Indeed, our data extend this concept to the entire population of mitochondrial patients, in addition to those with PEO; furthermore, we show that a "mitochondrial neuropathies" are predominantly associated with a few specific nuclear genes associated: POLG, TYMP and SURF1.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Progressive external ophthalmoplegia is the the most common disorder of cranial musculature and is seen with both nuclear and mitochondrial DNA mutations w76. The presence of Duane syndrome, a congenital and non-progressive strabismus with a mild sensory and motor axonal neuropathy is seen with dominant mutations in TUBB3 w77…”
Section: Introductionmentioning
confidence: 99%